Characteristics of Asprosin and Some Biochemical in Prediabetic Pregnant Women Presenting with UTIs - Al-Sultan, Lamia H.A.; Hassan, Nour Saeed (Newinera Publisher, 2024)
Diabetes can exacerbate the infection since pregnant women with diabetes had a higher incidence of UTI (29.9%) than pregnant women without diabetes (11.1%). This study investigated the percentage of patients who had a urinary tract infection (UTI) in order to evaluate the function of paternal genetics in the development of DM and ascertain the effect of DM on the urinary system. The study comprised 90 pregnant women, ages 25 to 50, with and without diabetes mellitus (DM) in comparison to control pregnant women. The blood sugar levels and diabetes mellitus were determined both clinically and in a private, specialized laboratory. There was information on the age, etiology, and family history of diabetes. Bacterial species were isolated and identified using culture media and biochemical assays. Patients with UTIs were mostly female (73%) in proportion. To sum up, type 2 diabetes is the most prevalent, particularly in women, and it rises with age. Family genetic susceptibility and abrupt shocks were the primary causes of diabetes mellitus. The majority of diabetes individuals, particularly women, experienced UTIs, and the primary reasons of UTI inflammation were also shown by the current study. Insulin-resistant mice and humans have pathologically elevated levels of asprosin, a new hormone that has been found to be concentrated in white adipose tissue. However, there is currently no information available about asprosin's involvement in type 2 diabetes mellitus (T2DM). The aim of our study was to determine whether there might connection between prediabetic pregnant women presenting with and circulating asprosin levels.